New directions for development in Third World countries : the failure of US foreign policy - Torres, James F. (Avebury, 1993)
After more than 40 years of assistance and investment by the developed nations the gap between rich and poor nations has increased. This text examines the reasons for this phenomena and proposes more effective ways to direct foreign assistance efforts in the future.